PERANAN HUKUM INVESTASI DALAM MENINGKATKAN PENANAMAN MODAL DI INDONESIA - MUHAMMAD ARIF PRASETYO PRASETYO (jurnal.unprimdn.ac.id, 2021)
Foreign investment has a very important role, considering that a developed country still needs investment, especially a developing country. District and City Governments throughout Indonesia, explore the potential of their respective regions in order to carry out promotions, so that they will be able to attract investment enthusiasm in investing. Following up on this desire, the respective Regency/City Governments issue Regional Regulations (called Perda), in order to increase Regional Original Income (PAD), regardless of the interests of the community and other impacts. The target of increasing PAD is the community and investors in general. on the authority of the Regency/City area, finally competing to issue regional regulations (Perda) without taking into account other aspects, which can hinder investment in their respective regions. Among other things, regional regulations regarding parking fees, street lighting fees and licensing in the trade and investment industries.